SYMPATHETIC NERVOUS SYSTEM ACTIVATION UNDER CHRONIC STRESS AND ITS SYSTEMIC EFFECTS ON THE HUMAN BODY (Global Conference on Medical and Health Sciences, 2026)
Background: Chronic psychological stress has emerged as a critical contributor to systemic physiological dysregulation, with the sympathetic nervous system (SNS) serving as a primary mediator of the stress response. Prolonged SNS hyperactivation exerts deleterious effects across multiple organ systems, including the cardiovascular, immune, endocrine, and gastrointestinal systems. Objective: This study aimed to comprehensively examine the physiological mechanisms underlying SNS activation in chronic stress and to evaluate its downstream systemic consequences. Methods: A systematic review of 10 key peer-reviewed studies published between 2012 and 2024 was conducted, focusing on neuroendocrine stress pathways, autonomic dysfunction, and associated organ-level pathophysiology.
Keywords: chronic stress; sympathetic nervous system; catecholamines; autonomic dysfunction; HPA axis; cardiovascular physiology; immunosuppression; neuroendocrinology